Chronic care management of globesity: promoting healthier lifestyles in traditional and mHealth based settings - Castelnuovo, Gianluca; Pietrabissa, Giada; Manzoni, Gian Mauro; Corti, Stefania; Ceccarini, Martina; Borrello, Maria; Giusti, Emanuele M.; Novelli, Margherita; Cattivelli, Roberto; Middleton, Nicole A.; Simpson, Susan G.; Molinari, Enrico (Frontiers in Psychology, 2015)
Obesity and being overweight could be real chronic conditions above all if there are other complications such as type 2 diabetes, cardiovascular diseases, hypertension, dyslipidemia, hypercholesterolemia, cancer and various psychosocial and psychopathological disorders,. Due to the multifactorial etiology of obesity, evidence-based interventions to improve weight loss, maintain a healthy weight, and reduce related comorbidities combine different treatment approaches: dietetic, nutritional, physical, behavioral, psychological, and, in some situations, pharmacological and surgical. There are significant limitations in this multidisciplinary chronic care management of obesity, most notably those regarding costs and long-term adherence and efficacy. Programs including eHealth platforms and new technologies could overcome limitations connected to the traditional in-patient chronic care management of obesity, thus providing promising opportunities in enhancing weight reduction and reducing complications in terms of long-term efficacy and effectiveness across clinical, organizational, and economic perspectives.